Research of the Mothed of Finite Element Modeling of an Electric Automotive Powertrain - Fang Yuan; Zhang Tong; Yu Peng; Guo Rong (Jixie chuandong)
As one of the major vibration and noise sources of electric vehicle,the powertrain is the key to NVH studies. The accurate calculation of the powertrain vibration modes and natural frequency are the foundation of lowering electric vehicle vibration and noise. The finite element model（ FEM） of motor and reducer are established and using four different ways of connection,the finite element modeling method of the centralized drive pure electric vehicle powertrain is discussed,meanwhile the effect of spot welding unit parameter on nature frequency is analyzed. Finally,through the comparing and analyzing the calculation result of the modal hammer test and finite element method,the feasibility of modeling method is testified. Combined with the vibration test,it is proposed that the transmission system should be considered in NVH studies since its effect on the inherent characteristic of powertrain shell. The results provided a foundation for the subsequent dynamic response analysis.